High levels of self-reported prescription opioid use by HIV-positive individuals. Issue 12 (1st December 2016) - Turner, Abigail Norris; Maierhofer, Courtney; Funderburg, Nicholas T.; Snyder, Brandon; Small, Kristi; Clark, Jan; Bazan, Jose A.; Kwiek, Nicole C.; Kwiek, Jesse J.
ABSTRACT: Prescription medication use (other than antiretroviral therapy (ART)) is highly prevalent among people living with HIV. Prescription medications may be used medically or non-medically: non-medical use includes using more medication than prescribed, using medication prescribed to someone else, or using medication for a purpose other than its prescribed use. During 12 weeks in 2014–2015, we characterized medical and non-medical prescription medication use among HIV-positive patients attending an academic medical center ( n = 149) and a community clinic ( n = 105). Separately for the past year and the past month, these 254 participants self-reported their use of prescription opioids, sedatives, stimulants, anti-anxiety medications, antipsychotic medications, and erectile dysfunction medications. Respondents were largely male (91%), aged 40 or older (61%), identified as gay or bisexual (79%), and were men who have sex with men (85%). ART use was nearly universal (95%). Nearly half (43%) of participants reported medical use of prescription opioids; 11% of the opioid use was reported as non-medical use. Anti-anxiety medication use was also frequent, and differed by site: 41% of community-clinic responders reported medical use of anti-anxiety medications compared to 23% of hospital clinic respondents who reported medical use. Prescription sedative use was also approximately twice as high among community-clinic participants, with medical use reported by 43% of respondents and non-medical use by 12%; in comparison, at the hospital clinic, sedative use was reported by 18% (medical) and 7% (non-medical) of participants. Stimulant use was rare in both sites. No demographic characteristic was significantly associated with medical or non-medical use of any prescription medication. The current focus of many studies on only non-medical prescription medication use not only underestimates the widespread exposure of HIV-positive individuals to these drugs, but may also underestimate potential adverse effects of prescription medications in this population.